Examination criteria and calibration procedures for prevention trials of the Early Childhood Caries Collaborating Centers. (22nd May 2015) - Warren, John J.; Weber‐Gasparoni, Karin; Tinanoff, Norman; Batliner, Terence S.; Jue, Bonnie; Santo, William; Garcia, Raul I.; Gansky, Stuart A.; ,
Abstract: Objectives: To summarize diagnostic criteria and examiner training and calibration of the National Institute of Dental and Craniofacial Research‐funded Early Childhood Caries Collaborating Centers (EC4) and report examiner calibration results from 2010 to 2014. The EC4 at Boston University, University of Colorado, and University of California San Francisco are performing randomized controlled early childhood caries (ECC) prevention trials with caries as the main outcome measure. Methods: The EC4 with University of Iowa consultants developed standardized tooth and tooth surface status examination criteria for use in field conditions, examiner training materials, and examiner calibration and re‐calibration methodologies. Calibration and re‐calibration were performed with 1‐ to 5‐year‐old children in the San Francisco Mission District in which assessments from each examiner to be calibrated were compared with those from a single gold standard examiner from 2010 to 2014. Cohen's kappa statistic was used to determine inter‐examiner agreement. Results: A total of seven examiners were successfully (re)calibrated during that period, examining a total of 231 children. Overall unweighted Cohen's kappas for 10 surface conditions exceeded the criterion of 0.70. However, separate agreement for assessment of noncavitated lesions, as in other studies, was lower. Conclusions: An experienced multidisciplinary and multi‐institutional team was able to develop criteria and training materials to anticipate situations and field conditions the main trials would encounter. Examiners were successfully trained and (re)calibrated.